Effect of urokinase type plasminogen activator on in vitro bovine oocyte maturation - Roldan Olarte, Eugenia Mariela (2017)
This study examines the impacts of the urokinase-type plasminogen activator (uPA) on the in vitro maturation (IVM) of bovine oocytes. Cumulus–oocyte complexes in IVM medium were treated with uPA, amiloride (an uPA inhibitor), dimethyl sulfoxide (DMSO) or left untreated (control group). After 24 h of IVM, oocytes were recovered for testing or were in vitro fertilized and cultured to the blastocyst stage. The factors examined in all groups were: (i) oocyte nuclear maturation (Hoëscht staining); (ii) oocyte cytoplasmic maturation (cortical granules, CGs, distribution assessed by LCA-FITC); (iii) oocyte and cumulus cell (CC) gene expression (RT-qPCR); and (iv) embryo development (cleavage rate and blastocyst yield). Oocytes subjected to uPA treatment showed rates of nuclear maturation and CG distribution patterns similar to controls (P> 0.05), whereas lower rates of oocyte maturation were recorded in the amiloride group (P< 0.05). Both in oocytes and CC, treatment with uPA did not affect the transcription of genes related to apoptosis, cell junctions, cell cycle or serpin protease inhibitors. In contrast, amiloride altered the expression of genes associated with cell junctions, cell cycle, oxidative stress and CC serpins. No differences were observed between the control and uPA group in cleavage rate or in blastocyst yield recorded on Days 7, 8 or 9 post-insemination. However, amiloride led to drastically reduced cleavage rate (28.5% vs 83.2%) and Day 9 embryo production (6.0% vs 21.0%) over the rates recorded for DMSO. These results indicate that the proteolytic activity of uPA is needed for successful oocyte maturation in bovine.